(untitled) (The Strategic Review for Southern Africa, 2020)
This publication, which consists of an Introduction and eight chapters by different authors, appeared at the time of the 40th anniversary of the entry of South Africa into the Angolan war. It is short but packed with useful information and well-documented with photos, geographical and combat maps, an extensive bibliography of 35 pages, political cartoons and posters, historical surveys and statistics. Edited by the South African Ian Liebenberg (Director of the Centre for Military Studies at the Military Academy in Stellenbosch), the Cuban Jorge Risquet (who participated in the 1988 Angolan peace talks), and the Russian Vladimir Shubin (former Deputy Director of the Institute for African Studies at the Russian Academy of Science), A Far-Away War sheds new light on this prolonged conflict, focusing on the involvement of South-Africa, Cuba, Russia and East-Germany. In doing so, it opens new perspectives and widens the understanding of the struggle for liberation in Southern Africa, not only for the average history and politics reader but also, as a very useful reference book, for the more advanced researcher and academic.